Pedagogical Effects Of Moving (National) Game On The Process Of Physical Training And Education - М.Yu.Gafurova (Research Parks Publishers, 2021)
The article argues that the pedagogical impact of mobile (national) play on physical education and learning process is that mobile games are a very effective tool in the process of physical education to bring up children in a healthy, active way through mobile games